THE EFFECT OF HEALTH EDUCATION ABOUT MENOPAUSE AGAINST READINESS IN FACING MENOPAUSEIN CLIMACTERIUM MOTHER IN MOJOROTO BUJEL PMB KEDIRI CITY IN 2019 - Siswi Wulandari (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Menopause is a period experienced by women when they will enter old age. Women will first encounter climacteric period. Data from a total of 100 climacteric mothers who examined health units 65 of them experienced physical and psychological complaints (SKRT, 2005). The impact that arises on someone's readiness in facing menopause is a lack of mental readiness such as lack of self-confidence, anxiety, and stress due to changes, upper neck and chest, difficulty sleeping, lack of concentration, depletion of the vaginal wall due to reduced estrogen, decreased sexual desire(1). The solution that can be done to overcome the lack of readiness in the face of menopause is to provide counseling to climacteric mothers. The purpose of this study was to determine the effect of health counseling about menopause on readiness in coping with menopause in climacteric mothers. This research is a pre-experimental research with One Group Pre Test Post Test Design approach where researchers can test whether there are changes that occur after the treatment. The results of the study were that of the 16 respondents obtained half of the respondents 8 people (50.0%) were in the category of not ready. There is an influence of counseling about menopause on readiness to face menopause in climacteric mothers.Keywords: Climacteric mother, Menopause, Health Counseling